Current Insight of Printability Quality Improvement Strategies in Natural-Based Bioinks for Skin Regeneration and Wound Healing - Masri, Syafira (Polymers (Basel), 2021)
Skin tissue engineering aimed to replace chronic tissue injury commonly occurred due to severe burn and chronic wound in diabetic ulcer patients. The normal skin is unable to be regenerated until the seriously injured tissue is disrupted and losing its function. 3D-bioprinting has been one of the effective methods for scaffold fabrication and is proven to replace the conventional method, which reported several drawbacks. In light of this, researchers have developed a new fabrication approach via 3D-bioprinting by combining biomaterials (bioinks) with cells and biomolecules followed by a suitable crosslinking approach. This advanced technology has been subcategorised into three different printing techniques including inject-based, laser-based, and extrusion-based printing. However, the printable quality of the currently available bioinks demonstrated shortcomings in the physicochemical and mechanical properties. This review aims to identify the limitations raised by using natural-based bioinks and the optimum temperature for various applied printing techniques. It is essential to ensure maintaining the acceptable printed scaffold property such as the optimum pore sizes and porosity that allow cell migration activity. In addition, the properties required for an ideal bioinks design for better scaffold printability were also summarised.